DYNAMICS OF SOIL NUTRIENTS AND ECTO-MYCORRHIZAL SYMBIONTS IN DISTURBED AND UNDISTURBED STANDS OF TROPICAL DRY DECIDUOUS FOREST OF CENTRAL INDIA - BHAVANA DIXIT; RASHMI AGARWAL (International Journal of Pharma and Bio Sciences, 2013)
The present investigation has been designed to study the influence of nutrients on formation and growth of ecto-mycorrhiza in disturbed and undisturbed stands of Tropical Dry Deciduous Forest of Central India with respect to soil moisture, pH, total organic carbon, organic matter, available Nitrogen and Available Phosphorus. Moisture content, pH, total organic carbon, organic matter, available Nitrogen and P decreased with increasing soil depth. All the soil parameters were higher in undisturbed site than the disturbed site, which is an indication of better productivity of the site. Negative correlation was found between soil depth and mycorrhizal count both for live and dead mycorrhiza. In most of the regression equations, r-values are significant (p<0.01) with a little error. Correlation between mycorrhizal counts (live and dead total) and available Nitrogen, organic matter and Phosphorus were highly significant. Occurrence of mycorrhizal roots is higher being in 5-10 cm depth (329±0.8) due to availability of optimum conditions for the development including higher organic matter percent. The rate of destruction of mycorrhizal roots increased with soil depth. Correlation coefficient value between soil depth and dead and live mycorrhizal roots are negatively significant. It may be due to low aeration, moisture content, organic matter and nutrient level.